Capturing Patient Reported Outcomes Following Treatment of Benign Anorectal Disease Requires Significant Surgeon Commitment: Do Surgeons Really Want to Know? - Thomas Peponis; Marc S. Rubin; Ronald Bleday; Harrison T. Hubbell; Robert N. Goldstone; Joel E. Goldberg; Khawaja F. Ahmed; Liliana G. Bordeianou (World Journal of Colorectal Surgery)
Background: The long-term effects of anorectal disease management on patients’ quality of life remains poorly understood. Objectives: This study aimed to evaluate the self-reported impact of both medical and surgical interventions for benign anorectal disease, using a standardized set of validated questionnaires. These questionnaires measure various domains, including pain, constipation, fecal incontinence, bleeding, leakage, protrusion, and overall quality of life. Design: Prospective, survey-based study. Setting: The colorectal surgery collaborative, involving two academic and three community hospitals. Patient and Methods: The study included all patients who presented to the clinic with benign anorectal disease between December 2017 and September 2019. Main Outcome Measure: The primary outcomes measured were the rates of adverse events and quality of life. Sample Size: A total of 811 individuals were invited, of whom 583 (71.9%) agreed to participate. Results: Diagnoses among participants were as follows: hemorrhoid (369 individuals, 28.8%), fistula (283 individuals, 22.1%), fissure (116 individuals, 9.0%), and other conditions (515 individuals, 40.1%). Nonoperative treatment significantly improved only the bleeding score (P = .046) but had no significant effect on the pain intensity score (P = .09), pain interference score (P = .084), itching score (P = .463), leakage score (P = .621), protrusion score (P = .083), bowel incontinence score (P = .737), constipation score (P = .61), or quality of life score (P = .211). Operative treatment for hemorrhoids resulted in significant improvements in the pain intensity score (P = .012), pain interference score (P = .015), bleeding score (P = .007), protrusion score (P = .006), and quality of life score (P = .001). Operative treatment for fistulas led to significant improvements in the pain intensity score (P = .046), pain interference score (P = .025), leakage score (P = .035), and quality of life score (P = .006). Only four patients who underwent operative treatment for fissures completed the postoperative questionnaire, and thus, no data could be presented on the impact of operative treatment for fissures. Conclusion: The routine use of patient-reported outcomes following the evaluation and treatment of classic anorectal conditions may enhance the understanding of patient’s perspective and their experiences with both medical and surgical interventions. Limitations: This study is limited by the lack of robust long-term follow up data, use of certain nonvalidated questionnaires, and potential for selection bias, as dissatisfied patients may have sought treatment at other centers. Conflict of Interest: The authors declare no conflict of interest.